Mistress by midnight ebook - Robinson, Maggie (Courtesan Court, 2011)
First comes seduction. . . As children, Desmond Ryland, Marquess of Conover, and Laurette Vincent were inseparable. As young adults, their friendship blossomed into love. But then fate intervened, sending them down different paths. Years later, Con still can't forget his beautiful Laurette. Now he's determined to make her his forever. There's just one problem. Laurette keeps refusing his marriage proposals. Throwing honor to the wind, Con decides that the only way Laurette will wed him is if he thoroughly seduces her. . . Then comes marriage. . . Laurette's pulse still quickens every time she thinks of Con and the scorching passion they once shared. She aches to taste the pleasure Con offers her. But she knows she can't. For so much has happened since they were last lovers. But how long can she resist the consuming desire that demands to be obeyed. . .? Praise for Maggie Robinson's Mistress by Mistake "Sizzles off the page." —Anna Campbell